Analisis Tingkat Pengetahuan Mahasiswa Pembinaan Prestasi Renang Fkor Universitas Sebelas Maret Tentang Teknik Dasar Gaya Dada - Muhammad Saifuddin ‘ Ittaqy; Agus Kristiyanto; Abdul Aziz Purnomo Shidiq (Educative Sportive, 2026)
Why do swimming performance development students continue to make technical errors despite undergoing intensive training? This question motivated an investigation into the level of cognitive competence among Swimming Performance Development students at the Faculty of Sports Sciences (FKOR), Universitas Sebelas Maret (UNS), in understanding fundamental breaststroke techniques. Using a quantitative descriptive survey design, data were collected from 35 students through a ten-item multiple-choice knowledge test administered via Google Forms. The data were analyzed using validity testing (Pearson correlation: r ≥ 0.30; p < 0.05), reliability testing (Cronbach’s Alpha: α = 0.78), and descriptive statistical procedures. The results showed a relatively wide distribution of breaststroke technique knowledge: 31.4% of students achieved an “Excellent” category (scores 9–10), 25.7% fell into the “Good” category (7–8), 22.9% into the “Fair” category (5–6), 17.1% into the “Poor” category (3–4), and 2.9% into the “Very Poor” category (0–2). The overall mean score was 6.69 (SD = 1.57). Although more than half of the respondents (57.1%) demonstrated knowledge at the good to excellent level, a notable proportion of students continued to struggle with conceptual understanding. These findings contribute to the development of instructional strategies that are responsive to variations in students’ cognitive performance within swimming performance development programs in sports education institutions.